The Transformation of Religious Authority: A Critical Review of Fanaticism and Intellectual Freedom in Indonesian Islamic Boarding Schools - Hani Hasnah Safitri; Ulul Albab; Abdul Khobir; Solehuddin, Moh. Sugeng; Adam Abd. Azid, Muhammad Adam Abd. Azid; Khimmataliev, Dustnazar Omonovich (Hayula: Jurnal Indonesia Studi Islam Multi-disiplin, 2026)
The transformation of religious authority in Indonesian pesantrens has significant implications for fanaticism and intellectual freedom. Using a hermeneutic-critical approach and Foucauldian discourse analysis, the kyai–santri relationship is interpreted as a practice of power and knowledge that shapes religious truth while reproducing hierarchical epistemic structures. Findings indicate that pesantren authority serves a dual function: preserving Islamic scholarly and moral traditions while potentially constraining students’ intellectual autonomy through epistemic compliance. The symbolic representation of kyais in modern media, along with students' subtle forms of resistance, signals a shift from charismatic-hierarchical authority to a participatory model. Pedagogical and curricular strategies such as dialogic learning, reflective halaqah, problem-based learning, and the integration of critical Islamic traditions—such as ijtihad and munāẓarah—are recommended to support this transition. By combining Foucault’s theory of power and knowledge with the principle of intellectual freedom in Islamic epistemology, a humanistic and emancipatory framework for Islamic education is presented. This approach positions pesantrens not merely as guardians of religious orthodoxy but as reflective learning spaces that foster critical awareness, ethical dialogue, and participatory spirituality within contemporary Muslim communities